Enriching the Competitive Advantage of the Bachelor of Science in Office Administration Students in Stenography: A Case Study in Camarines Sur Politechnic College, Philippines - Jaira Jovi E. Sayson; Ray John N. Villar; Glydia Alecx R. Boado; Alyssa De Loyola–Lagatic (Advances in Psychological Sciences and Applications, 2026)
This research focused on enriching the competitive advantages of BSOA students in stenography in CSPC. The respondents of this study were the one hundred seventy-four (174) second-year and third-year Bachelor of Science in Office Administration Students (BSOA) students at Camarines Sur Polytechnic Colleges (CSPC). The researchers used a descriptive method and employed different statistical tools, such as the frequency and percentage technique, the percentage ranking method, and Kendall’s Coefficient of Concordance. In the competitive advantages of BSOA students along transcription, most of the students have excellent skills in stenography with 37.36 percent, followed by the students with fair transcription skills with 27.59 percent, students who need improvement with 18.97 percent, and students with satisfactory skills with 16.09 percent. Meanwhile, in dictation, the majority of students have fair dictation abilities with 40.80 percent, followed by the students that needs improvement with 36.21 percent, students who have satisfactory skills with 7.32 percent, and students who have excellent skills with 6.32 percent. On the academic performance of the BSOA students, students with satisfactory grades in stenography have the highest frequency, with 48.85 percent, followed by students with fair grades, with 42.53 percent, students with excellent grades in stenography, with 4.60 percent, and students who still need improvement in stenography, with 4.02 percent. Further results revealed that there is a significant relationship between the competitive advantages and academic performance of BSOA students in stenography. As an output of the study, an instructional material was proposed to further enrich the competitive advantage of BSOA students in stenography in CSPC.